A sequential decomposition of the drop in collective bargaining coverage - Fitzenberger, Bernd; Sommerfeld, Katrin (Mannheim, 2015)
"Union representation has been in strong decline in most OECD countries with potentially important consequences for wages. What drives this decline? We try to answer this question by developing and implementing a detailed decomposition approach based on Fairlie (2005). Using linked employer-employee data from the German Structure of Earnings Survey for 2001 and 2006, we document a sharp drop in collective bargaining coverage that amounts to 17 percentage points for males and 20 percentage points for females in West, and eight and 14 percentage points, respectively, in East Germany. We find that neither changes in the characteristics nor changes in the coefficients associated with the characteristics as a whole provide an explanation for the drop in collective bargaining coverage. The drop in coverage is the result of an unexplained time trend."